Use of Methadone in Treating Chronic Noncancer Pain - Helen Hays; Mary Ann Woodroffe (Pain Research and Management)
Chronic, noncancer pain is often very difficult to treat. Opioids continue to be the most effective analgesics in relieving severe pain, and recently their long-term use has gained wider acceptance because patients report benefits related to improved comfort and/or enhanced function. There is no best choice of opioids, but rather analgesics are chosen according to individual needs and response. It may be beneficial to trial various opioids because of the possibility that opioid responsiveness may vary from drug to drug. The authors' clinical experiences using oral methadone and the switchover process from the previously used opioid to methadone are reported. This potent analgesic has a wide variation in elimination half-life and clearance. Consequently, there are inherent risks, such as severe sedation, in using opioid equianalgesic charts when switching to methadone from alternate opioids. Therefore, it is imperative that treatment be individualized, and that practitioners be familiar with prescribing opioids and have a good understanding of their pharmacokinetics. The authors' experiences are with an out-patient population, and the gradual changeover process that they use demonstrate safety without loss of pain control. This method may also be useful in those suffering terminal illness.